Hematology a pathophysiologic approach - Hudnall, S.David (Mosby physiology monograph series., 2012)
Delivers an understanding of hematolymphoid physiology and pathophysiology. This title offers you explanations of hematopoiesis, immunology, hemostasis, hemoglobinopathy, metabolic disorders, genetics, and neoplasia.